Identifying profiles of children at risk of being less physically active: an exploratory study using a self-organised map approach for motor competence. Issue 12 (18th June 2019) - Estevan, Isaac; García-Massó, Xavier; Molina García, Javier; Barnett, Lisa M.
ABSTRACT: This study aims to develop profiles in children according to physical fitness, actual and perceived motor competence, and to examine the level of engagement in physical activity and weight status according to these profiles. In the study, 156 typically developing Spanish children (47.4% girls) of primary school age (5–11 years-old) participated voluntarily. Children's perceived and actual motor competence, physical fitness, physical activity participation and weight status were assessed. A Self-Organising Map and K -means cluster analysis were used to classify and visualise the values. Four profiles were found: profile 2 was aligned – high capacity, high perception, profile 1 was partially aligned – medium capacity and perception, profile 3 and 4 were both non-aligned – low capacity, medium perception and medium capacity, low perception; respectively. Children in profile 2 were more active than children in profile 3 and 4 ( P < .05). In profile 2 there was a lower frequency of overweight/obese children than normal-weight children. On the contrary, in profiles 1, 3 and 4 a similar distribution of normal-weight and overweight/obese children was found. High capable children with high perception exhibited higher physical activity participation and were more likely to be of normal-weight compared to those with low capacity and/or perception.